Gender-specific genomic profiling in metastatic colorectal cancer patients treated with 5-fluorouracil and oxaliplatin. (January 2011) - Gordon, Michael A; Zhang, Wu; Yang, Dongyun; Iqbal, Syma; El-Khouiery, Anthony; Nagashima, Fumio; Lurje, Georg; Labonte, Melissa; Wilson, Peter; Sherrod, Andy; Ladner, Robert D; Lenz, Heinz-Josef
Aims: Survival and response rates in metastatic colorectal cancer remain poor, despite advances in drug development. There is increasing evidence to suggest that gender-specific differences may contribute to poor clinical outcome. We tested the hypothesis that genomic profiling of metastatic colorectal cancer is dependent on gender.Materials & methods: A total of 152 patients with metastatic colorectal cancer who were treated with oxaliplatin and continuous infusion 5-fluorouracil were genotyped for 21 polymorphisms in 13 cancer-related genes by PCR. Classification and regression tree analysis tested for gender-related association of polymorphisms with overall survival, progression-free survival and tumor response.Results: Classification and regression tree analysis of all polymorphisms, age and race resulted in gender-specific predictors of overall survival, progression-free survival and tumor response. Polymorphisms in the following genes were associated with gender-specific clinical outcome: estrogen receptor β, EGF receptor, xeroderma pigmentosum group D, voltage-gated sodium channel and phospholipase A2.Conclusion: Genetic profiling to predict the clinical outcome of patients with metastatic colorectal cancer may depend on gender.